Green infrastructure - Thorne, Nigel (4D Journal of Landscape Architecture and Garden Art, 2012)
Within the United Kingdom, Natural England is a quasi-non-governmental organisation that has the expertise and resource to advise the government via practical, researchbased evidence on best-practice operations relating to the safeguarding of England’s natural ‘wealth’ for the benefit of everyone. A government advisor on the ‘natural’ landscape and environment whose aim is to ensure the environment is able to adapt, adopt and survive for future generations, allowing people and nature to thrive.